Enhancing Ice Nucleation: The Role of Surface Roughness in Electrofreezing Using Laser Shock Processed Al6061 T6 Electrodes - E. G. Espinosa-Yañez; G. C. Mondragón-Rodríguez; E. José-Trujillo; D. P. Luis (Applied Sciences)
The present study investigates the impact of the electrode surface roughness on the electrofreezing of water. This research focuses on how the electrode microstructure induced by a laser treatment affects the nucleation and growth of ice crystals under controlled electric fields. For this, electrofreezing experiments of deionized water over electrodes with varying surface roughnesses and crystalline textures were conducted. The electrodes of the Al6061 T6 alloy were microstructured via the Laser Shock Processing (LSP) method. For this purpose, the pulse densities during the LSP process were varied (900, 1600, and 2500 pulses/cm2). The increase in pulse density was correlated to the microstructural features and average roughness of the LSP-treated Al6061 alloy. A wave-like microstructure was induced upon the LSP treatment, with roughnesses between 3.5 and 6 µm at the selected pulse densities. The results indicate that electrode roughness significantly influences the electrofreezing process. Rougher electrodes were found to increase the nucleation temperature, suggesting enhanced ice nucleation activity. These findings are attributed to the increased electric field concentration at the asperities of the rough surfaces and the (111) planes of the Al6061 alloy, which may facilitate the alignment of water molecules and the formation of critical ice nuclei.